Effects of Different Doses of High-Speed Resistance Training on Physical Performance and Quality of Life in Older Women: A Randomized Controlled Trial - Garcia-Hermoso, A (Dove Medical Press Ltd., 2016)
Objective: This study aimed to compare the effects of two frequencies of high-speed resistance training (HSRT) on physical performance and quality of life of older women. Methods: A total of 24 older women participated in a 12-week HSRT program composed of either two or three sessions/week (equated for volume and intensity). Women were randomized into three arms: a control group (CG, n=8), a resistance training group performing two sessions/week (RT2, n=8), and a resistance training group performing three sessions/week (RT3, n=8). The training program for both experimental groups included exercises that required high-speed concentric muscle actions. Results: No baseline differences were observed among groups. Compared with the CG, both training groups showed similar small to moderate improvements (P<0.05) in muscle strength, power, functional performance, balance, and quality of life. Conclusion: These results suggest that equated for volume and intensity, two and three training sessions/week of HSRT are equally effective for improving physical performance and quality of life of older women. © 2016 Ramirez-Campillo et al.